2017
DOI: 10.1111/epi.13912
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal coupling of ripples and slower oscillations during sleep in patients with focal epilepsy

Abstract: Summary Objective Differentiating pathological and physiological high-frequency oscillations (HFOs) is challenging. In patients with focal epilepsy, HFOs occur during the transitional periods between the up and down state of slow waves. The preferred phase angles of this form of phase-event amplitude coupling are bimodally distributed, and the ripples (80–150 Hz) that occur during the up-down transition more often occur in the seizure onset zone (SOZ). We investigated if bimodal ripple coupling was also evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…Our study was not designed to determine whether MI (>150 Hz & 3‐4 Hz) is more useful than other interictal HFA measures. Some investigators have suggested that characterization of the angle of slow‐wave phase preferentially coupled with HFA was useful in localization of SOZ . For measurement of the amplitude of HFA, the present study employed a high‐pass filter of 150 Hz; thus, the amplitude of HFA 80‐150 Hz may have only modestly contributed to computation of MI (>150 Hz & 3‐4 Hz) .…”
Section: Discussionmentioning
confidence: 98%
“…Our study was not designed to determine whether MI (>150 Hz & 3‐4 Hz) is more useful than other interictal HFA measures. Some investigators have suggested that characterization of the angle of slow‐wave phase preferentially coupled with HFA was useful in localization of SOZ . For measurement of the amplitude of HFA, the present study employed a high‐pass filter of 150 Hz; thus, the amplitude of HFA 80‐150 Hz may have only modestly contributed to computation of MI (>150 Hz & 3‐4 Hz) .…”
Section: Discussionmentioning
confidence: 98%
“…17 HFOs, divided into ripples and FRs, were detected automatically using the MNI detector 19 (The detector is also implemented in RIPPLELAB 20 ). 17 HFOs, divided into ripples and FRs, were detected automatically using the MNI detector 19 (The detector is also implemented in RIPPLELAB 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ripples usually predominate during LVF, whereas fast ripples (FRs) are more frequent during PS seizures. 17 In our previous study, we demonstrated that in the interictal period, higher values of PAC exist in the SOZ compared to normal channels 13 ; however, how different types of epilepsy or seizures are associated with different coupling patterns has not been investigated yet. 7 Phase-amplitude coupling (the coupling between the amplitude of high-frequency activity and the phase of the lowfrequency band; PAC) has been the subject of many studies, not only in normal brain activity, but also in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 92%
“…37 Further studies considering preferred phase angles of coupling may explain the electrophysiological features and the detailed epileptic network activity of ES. 37 Further studies considering preferred phase angles of coupling may explain the electrophysiological features and the detailed epileptic network activity of ES.…”
Section: Limitationsmentioning
confidence: 99%